2021
DOI: 10.1038/s41436-020-01027-3
|View full text |Cite|
|
Sign up to set email alerts
|

An autosomal dominant neurological disorder caused by de novo variants in FAR1 resulting in uncontrolled synthesis of ether lipids

Abstract: In this study we investigate the disease etiology in 12 patients with de novo variants in FAR1 all resulting in an amino acid change at position 480 (p.Arg480Cys/His/Leu). METHODS: Following next-generation sequencing and clinical phenotyping, functional characterization was performed in patients' fibroblasts using FAR1 enzyme analysis, FAR1 immunoblotting/immunofluorescence, and lipidomics. RESULTS: All patients had spastic paraparesis and bilateral congenital/juvenile cataracts, in most combined with speech … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 27 publications
2
28
0
Order By: Relevance
“…Due to the rapid rate of progress of HSP research, new genes are being identified on a regular basis. Examples of recently identified HSP genes include UCHL1 (SPG79), UBAP1 (SPG80), SELENOI (SPG81), PCYT2 (SPG82), HPDL (SPG83), and those not yet assigned a locus (RNF170 and FAR1) [7][8][9][10][11][12][13][14][15][16]. Some genes are much rarer than others, and it cannot be excluded that certain mutations may be 'private' to individual families.…”
Section: Multiple Genes and A Rapidly Increasing Gene Listmentioning
confidence: 99%
“…Due to the rapid rate of progress of HSP research, new genes are being identified on a regular basis. Examples of recently identified HSP genes include UCHL1 (SPG79), UBAP1 (SPG80), SELENOI (SPG81), PCYT2 (SPG82), HPDL (SPG83), and those not yet assigned a locus (RNF170 and FAR1) [7][8][9][10][11][12][13][14][15][16]. Some genes are much rarer than others, and it cannot be excluded that certain mutations may be 'private' to individual families.…”
Section: Multiple Genes and A Rapidly Increasing Gene Listmentioning
confidence: 99%
“…In general, our participation in GeneMatcher has been a very positive Ferdinandusse et al, 2021). In all, we gathered twelve individuals (eight tested at GeneDx) with heterozygous de novo missense variants at the same residue.…”
Section: Outcomes Of Genematcher Participationmentioning
confidence: 99%
“…Though patients with FAR1 deficiency have not exhibited the skeletal phenotype of RCDP, they present with developmental delay, microcephaly, seizures, growth retardation, cataracts, and spasticity reminiscent of the extra‐skeletal manifestations of plasmalogen synthesis defects 135 leading some to consider this disorder as RCDP type 4 137 . FAR1 overactivity was recently associated with a syndrome of spastic paraparesis, cataracts, and developmental delay 138 . Deficiency of alkylglycerol monooxygenase, the enzyme necessary for cleavage of ether linked FAs during recycling of ether lipids, can cause a disorder characterized by microcephaly, developmental delay, and short stature 139 .…”
Section: Physiological Pathways and Inherited Disordersmentioning
confidence: 99%
“…137 FAR1 overactivity was recently associated with a syndrome of spastic paraparesis, cataracts, and developmental delay. 138 Deficiency of alkylglycerol monooxygenase, the enzyme necessary for cleavage of ether linked FAs during recycling of ether lipids, can cause a disorder characterized by microcephaly, developmental delay, and short stature. 139 RCDP and other phenotypes associated with skeletal, ophthalmological, and nervous system abnormalities can also be seen in other genetic disorders associated with peroxisome biogenesis outside the scope of this review but have been described in detail in other works.…”
Section: Ether Lipid Metabolismmentioning
confidence: 99%